Ethical Followership: An Examination of Followership Beliefs and Crimes of Obedience. (February 2013) - Carsten, Melissa K.; Uhl-Bien, Mary
This study seeks to "reverse the lens" in leadership and ethics research by investigating whether follower (rather than leader) characteristics are associated with intentions to engage in unethical behavior. Specifically, we examine whether followers' beliefs about the coproduction of leadership and the romance of leadership are related to their willingness to commit a "crime of obedience" by complying with a leader's unethical request. Using a vignette depicting an unethical demand by a leader, 161 working adults were asked to indicate whether they would obey or challenge the leader's request. Regression analyses show that individuals with weaker coproduction beliefs demonstrate a stronger intent to obey unethical requests, whereas individuals with stronger coproduction beliefs demonstrate a stronger intent to engage in constructive resistance. This relationship is partially mediated by displacement of responsibility. Findings also identify an interaction between followers' belief in the coproduction of leadership and romance of leadership, such that individuals with stronger coproduction beliefs who romanticize leaders reported a stronger intent to obey unethical requests. Results are discussed in relation to research on obedience to authority and burgeoning research on followership.